COMMUNITY PARTICIPATION IN MUSRENBANG ACTIVITIES AT THE CURIO SUB-DISTRICT LEVEL, ENREKANG REGENCY - Sanjaya, M. Lukman Arif; Guntur, Muhammad; Rukmana, Novayanti Sopia (Jurnal Aktor, 2025)
Community participation in Musrenbang is an important factor in regional development, not only as a tool for determining regional government development programs, but also as a control over regional development. The objectives of this research are: 1) To find out how the community participates in the implementation of Musrenbang at the Curio District level, Enrekang Regency; 2) Knowing the factors that influence the level of community participation in the implementation of Musrenbang at the Curio District level, Enrekang Regency. The type of research used is descriptive qualitative and the data collection methods are interviews and documentation. The number of informants in this research was 5 (five) people. Then data analysis techniques include data reduction, data presentation and verification or drawing conclusions. The research results show that: 1) The level of community participation in the implementation of Musrenbang in Curio District, Enrekang Regency is quite high, the community is actively involved in the implementation of Musrenbang by attending the implementation of Musrenbang and submitting opinions and suggestions regarding the work program that will be implemented for one year; and 2) Factors that influence the level of community participation in Musrenbang at the Curio District level in Enrekang Regency include: high community enthusiasm, easy access to information and adequate liaison between regions in Curio District, thereby facilitating community mobility which also supports community participation in Musrenbang, implementation of Musrenbang at the Curio District level.